Factors Affecting Consumer Satisfaction to Online Shopping - S. Santos, Kim Edward; Santos, Angelo R. (International Journal of Humanities and Education Development (IJHED), 2020)
Most companies are expanding their network through an online platform. Under various scenarios (e.g. pandemic situations), market vendors should be versatile and adaptable to different types of distribution channels. This paper described the factors affecting consumer satisfaction to online shopping such as reliability and responsiveness, assurance and empathy, and tangibility. This paper determined the significant difference between the sex of respondents and the factors affecting consumer satisfaction to online shopping. This paper used a descriptive method, a total of 487 online consumers (219 Male and 268 Female) within Cabanatuan City were involved in this study using adopted questionnaire with adopted likert-scale responses. Based on the gathered data, the researchers drew four conclusions. First, the respondents have a strong degree of confidence in their respective website/application for online shopping. Hence, it is recommended that owners of online shopping website/application should work on improving their order cancelation and returns. Second, the respondents trusted online shopping websites/applications because of their marketing tactics, such as word of mouth, to boost their credibility. Hence, it is highly suggested that the owners of online shopping website/application should track the problems involving product delivery. Third, respondents have been literate in using and searching online shopping websites/applications. Hence, it is recommended that the owners of the online shopping website/application continuously improve their system to keep their consumers satisfied. Finally, the null hypothesis is retained. It implies that sex does not affect the consumer satisfaction to online shopping factors. Thus, it is suggested to look for other variables that may affect consumer satisfaction.